Mindfulness Intervention for Child Abuse Survivors: A 2.5‐Year Follow‐Up. Issue 10 (20th May 2014) - Earley, Michael D.; Chesney, Margaret A.; Frye, Joyce; Greene, Preston A.; Berman, Brian; Kimbrough, Elizabeth
<x xml:space="preserve">Abstract</x> Objective The present study reports on the long‐term effects of a mindfulness‐based stress reduction (MBSR) program for adult survivors of childhood sexual abuse. Method Of the study participants, 73% returned to the clinic for a single‐session follow‐up assessment of depression, posttraumatic stress disorder (PTSD), anxiety, and mindfulness at 2.5 years. Results Repeated measures mixed regression analyses revealed significant long‐term improvements in depression, PTSD, anxiety symptoms, and mindfulness scores. The magnitude of intervention effects at 128 weeks ranged from d = .5 to d = 1.1. Conclusion MBSR may be an effective long‐term treatment for adults who have experienced childhood sexual abuse. Further investigation of MBSR with this population is warranted given the durability of treatment effects described here.